La intercomprensión de lenguas latinas: una herramienta para el desarrollo del plurilingüismo en Chile - Chávez, Gilda Tassara; Villalón, Carlos (Colombian Applied Linguistics Journal, 2014)
In the framework of Chile’s integration into the globalised world, progress in plurilingualism looms really large; particularly in the development of plural approaches, amongst which language intercomprehension is to be highlighted. Benefits of this approach application in the Chilean education are mentioned here, namely, principles, basis and characteristic elements of it; and main projects and programmes developed in Europe for more than 20 years and implementations in South America are subsequently presented. Interlat, the Chilean Handbook is succinctly described as well as the impressions of the students once the course is over.